221 Effect of age and rut period on the semen quality in reindeer (Rangifer tarandus). (5th December 2019) - Nikitkina, Elena; Musidray, Artem; Krutikova, Anna; Timofeeva, Svetlana; Plemyashov, Kirill; Anipchenko, Polina; Goncharov, Vasilii
Abstract: Reindeer herding is a traditional activity of the indigenous peoples of the Arctic. Assisted reproductive technology in reindeer herding are under development. This is due to the difficulty of collecting reindeer sperm (Rangifer tarandus) in the Arctic. The aim of the work was to study the influence of age and rut period on the quality of reindeer (Rangifer tarandus) sperm. Semen was collected in Taimyr in autumn 2017, 2018. Ejaculate volume, total (TM) and progressive motility (PM) and sperm concentration were evaluated. TM, PM and sperm concentration were measured by CASA (computer-assisted semen analysis). Sperm was not found in caudae epididymidae in males at the age of six months. The sperm was collected only from caudae epididymidae from males aged 1.5 and 2.5 years. Collecting of ejaculated semen is possible in males from 3.5 years of age. The volume of ejaculate increased from 0.3±0.09 ml (mean±SD) at the age of 3.5 years to 0.7±0.09 ml at the age of 5.5 years and older (P < 0.05). Concentration of cells increased by 2 times in older males. It is known that reindeer sperm can be collected only during the rut. At the beginning and end of the rut, the collection of sperm by electroejaculation was not always successful, sperm was collected in 3 of 10 cases, while in the middle of the rut in 9 of 10 cases. There was no significant effect of the rut period on the ejaculate volume and sperm concentration. The lowest TM (51.1±2.16%) and PM (33.5±7.90%) were at the beginning of the rut, the highest at the end (73.0±5.02% and 59.0 ± 6, 30%) (P < 0.01). Thus, the effect of age and rutting period on the reindeer sperm was observed. Authors acknowledge financial support from Russian Science Foundation, Grant No:17-16-01023.